LGBT Rights in Chile: Tensions in the constitution of sexualized otherness - Caterine Joanna Galaz Valderrama; Académica Universidad de Chile; Mauricio Sepúlveda Galeas; Universidad de Chile; Rolando Poblete Melis; Universidad Central de Chile; Lelya Troncoso Pérez; Universidad de Chile; Rodolfo Morrison Jara; Universidad de Chile (Escuela de Psicología, Pontificia Universidad Católica de Valparaíso, 2018)
This article presents an analysis of the latest laws passed in Chile that take sexual diversity into account, in addition to the discussions held in the respective parliamentary committees, where different social agents argued in favor or against them. The emergence of "sexual diversity" as a field of public action in Chile is described, together with how the notions of "difference" and "otherness" are articulated, with "sexual diversity" being its governmental translation. We conclude that in these policies emerge privileged forms of "otherness", based on sexuality constructions organized only around identitary recognition, with no articulation to other axes of differentiation/inequality. Likewise, non-heterosexual subjectivities are homogenized, thereby producing abject and invisible subjects for public policy. Hence, different fields of empirical study come along, referred to how these interpretation frameworks guide the intervention devices oriented to LGBTI population.